surrounded by narcissists Or, How to Stop Other People's Egos Ruining Your Life - Erikson, Thomas (Vermilion, an imprint of Ebury Publishing, 2022)
"Are you overshadowed by the narcissists in your life? Are you worn out by their constant demands for attention, their absolute belief they are right (even when clearly they are not), their determination to do what they want (regardless of impact), and their baffling need to control everyone and everything around them? In this thought-provoking, sanity-saving book, Thomas Erikson helps you understand what makes narcissists tick and, crucially, how to handle them without wearing yourself out in the process. With the help of the behavioural model made famous in Surrounded by Idiots, Erikson provides all the tools you need to manage not just the narcissists around you but everyday narcissism as well - itself becoming more widespread in this age of social media. Engaging and practical, Surrounded by Narcissists will help you free yourself from narcissistic agendas so you can pursue a happier, more fulfilling and successful life."-- Back cover.